Effect of Substitution of β-Glucans on the Glycemic Response and Thermal Properties of Four Common Starches - Alfred Anderson; Mariam Fouda (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2016)
Diabetes Mellitus (DM) is a major public health concern worldwide which can lead to a series of disabling complications and diseases. β-glucans are non-starch polysaccharides that are being used as food additives for their numerous health benefits including the ability to lower the postprandial glucose response. The aim of this study was to determine the effect of substituting β-glucans on the glycemic response and thermal properties of four commonly consumed starches. Oat β-glucans were added at concentration levels of 0%, 10%, 20%, and 30% (w/w) to each of the four starch types. Composite starches incubated with α-amylase followed by further incubation with amyloglucosidase. Glucose released was measured using the 3, 5-dinitrosalicylic acid (DNSA) method. Incremental Area under the Curve (iAUC) was used to represent the estimated glycemic response of the β-glucan/starch composites. Thermal analysis of the starch composite starches was conducted using a differential scanning calorimeter. An overall reduction in the amount of glucose released after the addition of β-glucans was observed (p ≤ 0.05). Substituting starches with 20% and 30% β-glucans resulted in a significant reduction in the glucose release rate and thus improved the estimated glucose response of all starches. A marked increase in the enthalpy of gelatinization, ΔH, of all starches was observed. Substitution at 10% β-glucans caused a significant increase in ΔH of blank tapioca starch (p ≤ 0.05). The 20% and 30% β-glucan samples also had significantly higher ΔH than the blank and the 10% β-glucan samples. The data from this study suggest the potential use of β-glucan as a suitable food ingredient in diabetic food products.